The Urgency of Codifying and Unifying Restorative Justice Regulations in Criminal Procedure Code Reform - Izharti, Rakhmi; Magdalena, Erika; Ramadhani, Rully Herdita (Faculty of Law Universitas Trunojoyo Madura, 2025)
The fragmentation of restorative justice regulations across Indonesia’s criminal justice institutions, including the police, prosecution, and judiciary, has resulted in procedural inconsistencies and undermined legal certainty for both victims and offenders. This study aims to examine the normative and institutional urgency of codifying and unifying restorative justice mechanisms within the reform of the Criminal Procedure Code (KUHAP), particularly in light of the restorative provisions introduced in the 2023 Code Penal (KUHP). Employing a normative juridical method, supported by limited empirical data from interviews with convicted persons, the research integrates statutory, comparative, and conceptual analyses to evaluate coherence between sectoral regulations and the integrated criminal justice framework envisioned by the revised KUHAP. Findings reveal significant regulatory divergence regarding eligibility criteria, procedural stages, and legal consequences, resulting in selective enforcement and a decline in public trust. The study concludes that codification and unification of restorative justice norms are imperative to harmonise institutional mandates, operationalise the principle of ultimum remedium, and ensure substantive legal certainty. Codified provisions should establish uniform procedures, binding legal effects, and cross-institutional coordination mechanisms. These reforms carry significant implications for advancing a humane and efficient criminal justice system in Indonesia, reducing litigation costs, and enhancing public confidence in restorative approaches.